"Real world" outcome of lenalidomide plus dexamethasone in the setting of recurrent and refractory multiple myeloma: Extended follow-up of a retrospective multicenter study by the "rete ematologica pugliese". Issue 3 (March 2015) - Mele, G.; Melpignano, A.; Quarta, G.; Palumbo, G.; Capalbo, S.; Falcone, A.; Cascavilla, N.; Palazzo, G.; Mazza, P.; Iannitto, E.; Curci, P.; Rizzi, R.; et al.
Highlights Study included patients excluded from trials because of unfavorable characteristics. 246 were evaluable for response and toxicity: 68% had relapsed MM, 32% refractory MM. OS was longer in patients receiving "lenalidomide + dexamethasone" for more than 12 months. Continuous treatment for at least 12 months was the best predictor of a longer OS.